MET Gain in Diffuse Astrocytomas is Associated with Poorer Outcome. (3rd July 2012) - Pierscianek, Daniela; Kim, Young‐Ho; Motomura, Kazuya; Mittelbronn, Michel; Paulus, Werner; Brokinkel, Benjamin; Keyvani, Kathy; Wrede, Karsten; Nakazato, Yoichi; Tanaka, Yuko; Mariani, Luigi; Vital, Anne; et al.
Abstract Glioblastoma may develop rapidly without evidence for precursor lesions (primary glioblastomas), or progress from diffuse or anaplastic astrocytomas (secondary glioblastomas). Despite having distinct genetic profiles, these glioblastoma subtypes have similar histological features. We hypothesized that the highly malignant phenotype of glioblastoma may be attributable to genetic alterations that are common to both glioblastoma subtypes. In the present study, we first searched for commonly (>35%) amplified genes in glioblastomas with IDH1 mutation (a hallmark of secondary glioblastoma) and those without IDH1 mutation (typical for primary glioblastoma) in data from The Cancer Genome Atlas (TCGA). A total of 25 genes were identified, of which 21 were located at 7q31‐34. We then screened 264 gliomas (70 glioblastomas, 112 diffuse astrocytomas, 82 oligodendrogliomas) for gain of the MET at 7q31.2 with quantitative polymerase chain reaction (PCR). MET gain was detected in primary glioblastomas (47%) and secondary glioblastomas (44%), suggesting that this genetic alteration plays a role in the pathogenesis of both glioblastoma subtypes. MET gain was also common in diffuse astrocytomas (38%), but less frequent in oligodendrogliomas (16%). MET gain in diffuse astrocytomas was associated with shorter survival (median, 43.0 vs. 70.7 months; P = 0.004), suggesting that MET gain is a useful prognostic marker for diffuse astrocytomas.